Length‐weight relationships of Acanthopagrus longispinnis (Valenciennes, 1830), Raconda russeliana (Gray, 1831) and Coilia neglecta (Whitehead, 1967) from the Bay of Bengal coast, Bangladesh. (20th May 2018) - Chaklader, M. R.; Siddik, M. A. B.; Hanif, M. A.; Nahar, A.; Islam, M. A.
Abstract: Current study reports the length‐weight relationships (LWRs) of three marine fish species collected from the fishermen catches covering three seasons i.e., rainy, autumn and winter between June, 2016 and February, 2017. Fishermen caught the species using beach seine net (3.5 cm mesh size) and set bag net (0.5 cm mesh size) up to 200 m far away from the shoreline. The LWRs for fish species were W = 0.0180TL 3.192 for A. longispinnis, W = 0.0109TL 2.971 for R. russeliana and W = 0.0098TL 2.942 for C. neglecta with their r 2 values of 0.971, 0.962 and 0.997, respectively.